2021
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105495
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome After Mechanical Thrombectomy with or without Previous Thrombolysis

Abstract: Introduction: Combined intravenous therapy (IVT) and mechanical thrombectomy (MT) is the standard treatment for acute ischemic stroke (AIS) with large vessel occlusion (LVO). However, the use of IVT before MT is recently being questioned. Objectives: To compare patients treated with IVT before MT with those treated with MT alone, in a real-world scenario. Methods: Retrospective analysis of AIS patients with LVO of the anterior circulation who underwent MT, with or without previous IVT, between 2016 and 2018. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…There was no statistical difference as regard recanalization rate, FPE, and puncture-revascularization time between both groups despite significantly shorter OPT in BT group because most of the patients in the dMT group presented to the emergency room late (outside the 4.5 h window). Similar results from other retrospective and real practice studies were reported with shorter OPT in BT group and similar www.nature.com/scientificreports/ baseline characters in both groups 17,18 . This could represent a theoretical advantage for better outcomes in BT group, however, our analysis does not confirm the effect of OPT in early (at day seven) or late (90-day) favorable outcomes (Tables 2, 3).…”
Section: Discussionsupporting
confidence: 89%
“…There was no statistical difference as regard recanalization rate, FPE, and puncture-revascularization time between both groups despite significantly shorter OPT in BT group because most of the patients in the dMT group presented to the emergency room late (outside the 4.5 h window). Similar results from other retrospective and real practice studies were reported with shorter OPT in BT group and similar www.nature.com/scientificreports/ baseline characters in both groups 17,18 . This could represent a theoretical advantage for better outcomes in BT group, however, our analysis does not confirm the effect of OPT in early (at day seven) or late (90-day) favorable outcomes (Tables 2, 3).…”
Section: Discussionsupporting
confidence: 89%
“…However, the mechanical thrombectomy alone group failed to show a favorable functional outcome among patients with acute large vessel occlusion stroke compared with the combined group. Furthermore, a recent finding supported the hypothesis that intravenous therapy before mechanical thrombectomy does not influence the prognosis of patients with stroke (126).…”
Section: Clinical Managementmentioning
confidence: 71%